2011
DOI: 10.1517/14740338.2011.583916
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of clinical decision support for the detection of drug–drug interactions

Abstract: DDI knowledgebases need to take into account more patient-specific information. Strategies to avoid alert fatigue, such as DDI tiering and reducing signal:noise ratios, are important areas for future study. End-user participation and clinician feedback should be incorporated in the development of DDI knowledgebases to increase alert compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 37 publications
1
99
0
1
Order By: Relevance
“…Other studies of decision support systems showed that these do not perform as expected [29] . Inappropriate timing and need to click to access information [24] and alert fatigue [30] were reported as the main reasons. Improving the human-computer interface, providing recommendations for patients in addition to practitioners [31] , prioritizing and filtering recommendations for the user [32] can improve the effectiveness of CDSS interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of decision support systems showed that these do not perform as expected [29] . Inappropriate timing and need to click to access information [24] and alert fatigue [30] were reported as the main reasons. Improving the human-computer interface, providing recommendations for patients in addition to practitioners [31] , prioritizing and filtering recommendations for the user [32] can improve the effectiveness of CDSS interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive values, especially the positive predictive value in the case of CPOEs, is closely linked to the prevalence of the alert considered. This has been demonstrated for drug-drug interactions decision support that has a very low positive predictive value [204,205]. Using the characteristics of the local population of patients of a given organization can provide precise and real-time prevalence, thus allowing to adapt decision support and improve its positive predictive value.…”
Section: H Clinical Practice and Research Integrationmentioning
confidence: 99%
“…This approach, however, needs refinement as patient-specific information is often lacking and data on current medications rely on different sources, for example, patient, carer and doctor, particularly in the acute setting. Moreover, several drug--drug interactions are unlikely to be clinically significant, with potential for over-reporting [18,19]. At least two recently developed strategies, that is, medication reconciliation and trigger tools methodology, might help to mitigate the impact of ADRs in this group by enhancing the monitoring of drug therapy in the context of acute changes in clinical status and organ function.…”
Section: Potential Strategies To Mitigate the Impact Of Adverse Drugmentioning
confidence: 99%